VITALITY: impact of adalimumab on health and disability outcomes in patients with Crohn's disease, rheumatoid arthritis, or psoriasis treated in clinical practice in New Zealand. (3rd October 2019) - Gearry, Richard B.; Frampton, Christopher; Inns, Stephen; Poppelwell, David; Rademaker, Marius; Suppiah, Ravi
Abstract: Objective: VITALITY, a 6-month, multicenter, prospective, observational study, assessed the effects of originator adalimumab (HUMIRA) on health and disability outcomes in patients with Crohn's disease (CD), rheumatoid arthritis (RA), or psoriasis treated in routine clinical practice in New Zealand (NZ). Methods: Biologic-naïve adults initiating adalimumab in accordance with NZ funding requirements were recruited. The primary endpoint was 6-month change from baseline in World Health Organization Disability Assessment Schedule (WHODAS) 2.0 score in all participants completing the study (full analysis set). Secondary endpoints included 6-month change in other patient-reported outcomes (PROs) of work activity and wellbeing (Work Productivity and Activity Impairment Questionnaire: General Health, Kessler Psychological Distress Scale, Flourishing Scale, and Subject Vitality Scale) and in disease-specific PRO measures. Results: In total, 164 participants with severe disease initiating adalimumab completed the WHODAS 2.0 at baseline, of whom 114 (69.5%) completed the study at 6 months. Mean WHODAS 2.0 score halved from 15.2 points ( SD = ±9.1) at baseline to 7.3 points ( SD = ±7.2) after 6 months' adalimumab treatment (mean difference = 7.9 points; 95% CI = 6.4–9.4; p  < .001), with statistically significant improvements seen as early as 2 months after adalimumab initiation ( p  < .001). The proportion of participants with a WHODAS 2.0 score ≥ 10 more than halved, from 68.3% to 28.9%, between baseline and 6 months. Other PROs also improved significantly at 6 months, as did disease-specific measures. No new adalimumab safety signals were observed. Conclusions: Health and disability outcomes improved significantly after 6 months of adalimumab use in NZ patients with severe CD, RA, or psoriasis. Clinicaltrials.gov: NCT02451839.